Correction of Pincer Nail Deformity Using Dermal Grafting - Nam, Hyun Min; Kim, Ui Kyung; Park, Seok Don; Kim, Jeong Hee; Park, Kun (Annals of dermatology, 2011)
Pincer nail deformity is characterized by excessive curvature and distortion of the nail in the transverse dimension, and particularly at the distal part of the nail plate. This deformity leads to pinching off and loss of soft tissue in the affected digit, causing severe pain. Many treatment methods have been proposed; however, an effective long-term method preserving the nail matrix has not yet been established. We present here a case of pincer nail in the left thumb in a 49-year-old woman who was treated successfully with dermal grafting under the nail bed. We describe the surgical method and the treatment results. To the best of our knowledge, this is the first report in the Korean medical literature on the use of dermal grafting for the treatment of pincer nail deformity.